Data and R code for estimating red fox (Vulpes vulpes) population density in Los Pilones and La Nava (Ciudad Real, Spain) using generalized spatial mark-resight models with incomplete identification (gen-SMR-ID) - Jose Jiménez; Richard Chandler; Jorge Tobajas; Esther Descalzo; Rafael Mateo; Pablo Ferreras (PANGAEA, 2019)
This dataset consists of a .zip folder containing all data files and R code for reproducing the spatial mark-resight with incomplete identification (gen-SMR-ID) analyses to estimate red fox population density and abundance in two places of Ciudad Real (Spain): La Nava and Los Pilones, and a separate dataset and R-code to test the new model using distance sampling in La Nava.
Supplement to: Jiménez, J et al. (2019): Generalized spatial mark–resight models with incomplete identification: An application to red fox density estimates. Ecology and Evolution, https://doi.org/10.1002/ece3.5077